QUALITY ANALYSIS OF THE GATE DIELECTRIC OF THE MOS-STRUCTURES BY CAPACITY-VOLTAGE CHARACTERISTICS - V. B. Odzhaev; A. N. Pyatlitski; V. S. Prosolovich; V. A. Filipenya; S. V. Shvedau; V. V. Chernyi; V. Yu. Yavid; Yu. N. Yankouski (Приборы и методы измерений)
There were investigated the capacity-voltage characteristics of the MOS transistors, fabricated by the similar process charts, with the identical applied technological materials), however at various time (appropriately further in the text series A and series B). It was shown, that the measurements of the capacityvoltage characteristics of the MOS structures make it possible to perform the quality diagnostics of the gate dielectric. The kind and shape of the measured characteristics are determined by the value of the additional positive charge in the dielectrics and density of the fast surface states on the Si-SiO2 interface, which correlate with the surface concentration of the technological impurities, adsorbed on the surface of the wafers in process of the devices fabrication, which makes it possible to make a conclusion about the quality of the applied materials and compliance of the manufacturing process.